CHARACTERS’ ANXIETY AND DEFENSE MECHANISMS OF THE GIRL ON THE TRAIN NOVEL: PSYCHOLOGICAL APPROACH - Dinar Rosiana Mareta; Anastasia Chika Alvina; Riefda Rainy Agustin; Emil Eka Putra (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
The goal of this research is to explore the anxiety and defence mechanisms of each female character in The Girl on The Train. The discussion is conducted through a psychological approach by applying Sigmund Freud’s (1926) and Anna Freud's (1993) theories of anxiety and defence mechanisms. The research is descriptive qualitative research. The data was collected by applying highlighting and note-taking techniques. The collected data are sentences which portray the anxiety and defense mechanisms performed by the female character in the story. The results of the analysis shows that (1) Rachel's character shows three forms of anxiety, which are neurotic, moral, and realistic; and three types of defence mechanisms, namely repression, denial, and displacement; (2) Megan’s character shows three forms of anxiety, which are neurotic, moral, and realistic; and shows two types of defence mechanisms, which are denial and displacement; and (3) Anna’s character shows one forms of anxiety, which is realistic; and shows two types of defence mechanisms, which are projection and rationalization.